In creatinine kinetics, the glomerular filtration rate always moves the serum creatinine in the opposite direction. Issue 16 (17th August 2021) - Chen, Sheldon; Chiaramonte, Robert
Abstract: Introduction: When the serum [creatinine] is changing, creatinine kinetics can still gauge the kidney function, and knowing the kinetic glomerular filtration rate (GFR) helps doctors take care of patients with renal failure. We wondered how the serum [creatinine] would respond if the kinetic GFR were tweaked. In every scenario, if the kinetic GFR decreased, the [creatinine] would increase, and vice versa. This opposing relationship was hypothesized to be universal. Methods: Serum [creatinine] and kinetic GFR, along with other parameters, are described by a differential equation. We differentiated [creatinine] with respect to kinetic GFR to test if the two variables would change oppositely of each other, throughout the gamut of all allowable clinical values. To remove the discontinuities in the derivative, limits were solved. Results: The derivative and its limits were comprehensively analyzed and proved to have a sign that is always negative, meaning that [creatinine] and kinetic GFR must indeed move in opposite directions. The derivative is bigger in absolute value at the higher end of the [creatinine] scale, where a small drop in the kinetic GFR can cause the [creatinine] to shoot upward, making acute kidney injury similar to chronic kidney disease in that regard. Conclusions: All else being equal, a change in the kinetic GFR obligates the [creatinine] to change in the opposite direction. This does not negate the fact that an increasing [creatinine] can be compatible with a rising kinetic GFR, due to differences in how the time variable is treated. Abstract : Changes in creatinine are tightly coupled to changes in kinetic GFR. From an established differential equation, the derivative of creatinine with respect to kinetic GFR was calculated. With it, we mathematically prove that all else being equal, if the kinetic GFR goes down, then the creatinine must go up, and vice versa. The two always move in opposite directions.